Assessment of the painDETECT questionnaire as a tool for screening and treatment evaluation in trigeminal neuralgia (Principles and Practice of Clinical Research, 2023)
Introduction: Although trigeminal neuralgia (TN) is diagnosed clinically and most cases can be easily identified, misdiagnoses are frequent and lead to delayed treatment. Therefore, we evaluated the painDETECT questionnaire, an established tool for detecting neuropathic pain components, as a screening tool in TN.Methods: We conducted a retrospective chart review of all patients who had presented to our neuro-surgical outpatient department complaining of craniofacial pain between January 2019 and August 2021. The patients were categorized as likely having TN (TN group) or likely having pain of a different etiology (non-TN). Patients with other neuropathic facial pain syndromes or those in whom TN could not be diagnosed nor ruled out with sufficient confidence were excluded. The painDETECT scores were compared, along with other outcome parameters.Results: We identified 52 patients with craniofacial pain. After exclusion of 14 patients, 25 patients were included in the TN group and 13 in the non-TN group. The mean painDETECT score was 17.0±4.7 and 12.7±6.1, respectively (p=0.02). The positive predictive value for TN at a cutoff value of 19 points was 80%, the negative predictive value was 39%. In patients who underwent surgery, the correlation between the postoperative painDETECT score and the postoperative numeric rating scale score was 0.73 (p=0.01).Discussion: The painDETECT questionnaire is of limited use as a screening tool for possible TN. It can be utilized to track treatment outcomes if data collection beyond daily clinical use is desired.Keywords: trigeminal neuralgia; facial pain; painDETECT questionnaire; neuropathic pain